Combination of pembrolizumab and lenvatinib in second-line therapy for MSS/pMMR advanced endometrial cancer: literature review and a case report - A. D. Darenskaya; B. M. Medvedeva; A. A. Rumyantsev (ABV-press, 2024)
Despite the existing standard treatments for endometrial cancer, the prognosis for these patients remained poor until recently. None of currently available cytostatics ensured long-term disease control and long-term survival of patients receiving standard platinum-based therapy. Poor treatment outcomes in patients with advanced endometrial cancer necessitated changes in therapeutic approaches and development of more effective treatment regimens. Better understanding of carcinogenesis mechanisms, emergence of a new molecular classification of endometrial cancer, and implementation of tailored treatment approaches based on tumor types led to a significant breakthrough in the treatment of advanced endometrial cancer. Currently, the most effective second-line therapy for endometrial cancer with high level microsatellite instability (MSI-h) or deficient mismatch repair system (dMMR) (25 % of cases), and no indications for surgery is pembrolizumab monotherapy. Most of cancers (about 75 %) are represented by microsatellite-stable and mismatch repair proficient tumors (MSS/рMMR). Patients with such tumors demonstrating disease progression after systemic therapy should receive a combinations of the immune checkpoint inhibitor pembrolizumab and the multi-targeted tyrosine kinase inhibitor lenvatinib. In this article, we review relevant literature and report a case of successful treatment of MSS/pMMR advanced endometrial cancer with a combination of pembrolizumab and lenvatinib as a second-line therapy (after disease progression in response to platinum-containing first-line chemotherapy), which ensured long-term disease control.